(untitled) (Journal of International Studies, 2024)
The objectives of the study are to examine the logistics activities of hai cut flower orchid exporters to Vietnam and evaluate their logistics performance across nine logistical operations in three dimensions: cost, time, and reliability. Identifying issues in improving the logistics efficiency of exporters is the key to gaining a competitive edge in exporting. Thai orchid exporters to Vietnam were interviewed in Bangkok, Nakhon Pathom, and Samut Sakhon provinces, Thailand’s main orchid production regions, using semi- structured interviews with open-ended questions. Quantitative and logistics management data were collected using the Agricultural Logistics Performance Index (ALPI), which evaluated nine logistics activities in three dimensions. Qualitative data were obtained from conceptual framework inquiries. Inductive analysis was used to study qualitative data, whereas percentages and averages were used to analyse quantitative data. According to the report, exporters performed six logistics tasks but ignored demand forecasting. Furthermore, site selection, warehousing and storage, and reverse logistics were absent. Exporter logistics performance averaged 94.98, with purchasing and procurement performing best at 98.05. Transportation, with an average performance of 90.84, needed the most optimisation. Exporters had the highest logistical reliability at 99.14, followed by cost and time.